Peran Dukungan Sosial Keluarga terhadap Berduka Kronis pada Lansia yang Mengalami Kehilangan Pasangan dalam Budaya Pakurenan - I Ketut Andika Priastana; Joni Haryanto; Suprajitno Suprajitno (Indonesian Journal of Health Research, 2018)
Introduction. One problem that often escapes attention is when the elderly experience a loss of spouse. This problem can cause psychological disturbance and if not done good handling will also affect the physical elderly. Bali is an area of Indonesia that has a distinctive culture associated residence called Pakurenan. This study analyzes the role of family social support and the resilience of elderly who suffer from chronic sorrow due to lost the partner in Pakurenan culture and the association between them. Methods. This cross-sectional study was conducted with 255 elderly in a simple random sample from a subdistrict in Bali in Indonesia. The data were collected from elderly who gave their informed consent to participate using a personal information form, the Perceived Social Support from Family (PSS-Fa) Scale and The Resilience Scale (RS). Data were assessed by descriptive statistics and Spearman's rho analyses, using SPSS software. Results. The mean age of the elderly in the study was 70.38 years (±5.159 years); 69% of the elderly were female, and 67.8% had low education level. The results indicated that there was a signiﬁcant positive correlation between the family social support and the resilience (rs = .993; p < .05). Conclusion. This study identiﬁed a signiﬁcant correlation between family social support and the resilience of elderly who suffer from chronic sorrow due to lost the partner in Pakurenan culture. This indicates that the family's social support in Pakurenan culture has a positive impact in increasing resilience in the elderly.